"SICERIA" BoMedia board game “SICERIA” dalam pembelajaran IPAS kelas V Sekolah Dasarard Game Media in Science Learning for Class V Elementary School - Fadhila, Nurul; Rezkita, Shanta; Djufri, Elyas (Trihayu: Jurnal Pendidikan Ke-SD-an, 2024)
Learning media in elementary schools is often neither innovative nor interactive. This presents a challenge for educators to design media that meets learning needs while engaging students. This research aims to develop board game-based learning media, "SICERIA," for fifth-grade elementary school IPAS subjects, specifically on the topic of the human digestive system. The study employed the Research and Development (R&D) methode with the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Data collection involved observations, interviews, and questionnaires with students, educators, and subject matter experts. The results indicate that SICERIA received very positive ratings, showing improvements in learning motivation, visual quality, and implementation. This media enhances students' understanding of the abstract concept of the human digestive system and fosters collaborative learning and social skill development. Despite limitations such as a narrow material scope and relatively high production costs, SICERIA offers an innovative alternative aligned with the Merdeka curriculum. The positive feedback from students suggests that SICERIA is not only pedagogically effective but also visually appealing and relevant to learning needs. This research contributes significantly to the development of game-based learning media to improve elementary school education. Keywords: board game media; SICERIA; IPAS